2023
DOI: 10.1186/s12984-023-01159-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation methods and protocols for the treatment of traumatic brain injury: a critical review of preclinical research

Abstract: Background Traumatic brain injury (TBI) is a leading cause of disabilities resulting from cognitive and neurological deficits, as well as psychological disorders. Only recently, preclinical research on electrical stimulation methods as a potential treatment of TBI sequelae has gained more traction. However, the underlying mechanisms of the anticipated improvements induced by these methods are still not fully understood. It remains unclear in which stage after TBI they are best applied to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 225 publications
0
2
0
Order By: Relevance
“…Our goal in reviewing TBI response to neurostimulation was to highlight limitations attributable to heterogeneous approaches and to raise the possibility of a more efficient, efficacious path. Similarly, previous reports have noted a wide variety of stimulation parameters have hindered the ability to draw comparisons between protocols and outcomes [1]. To accelerate the research and federal consensus on the mechanisms and proper research parameters for each condition, more interdisciplinary research that is mechanistically focused is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our goal in reviewing TBI response to neurostimulation was to highlight limitations attributable to heterogeneous approaches and to raise the possibility of a more efficient, efficacious path. Similarly, previous reports have noted a wide variety of stimulation parameters have hindered the ability to draw comparisons between protocols and outcomes [1]. To accelerate the research and federal consensus on the mechanisms and proper research parameters for each condition, more interdisciplinary research that is mechanistically focused is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The research will be further advanced by a systematic hypothesis-driven approach to experimental design regarding stimulation parameters. This review emphasizes the difficulty in synthesis and comparisons between protocols when there is little consistency in paradigms [1]. This issue can be remediated by integration across fields and with emphasis on mechanisms-even in the face of a heterogeneous condition like mTBI.…”
Section: Introductionmentioning
confidence: 99%
“…Seok Lew, Olivet Nazarene University, United States Maria-Carla Piastra, University of Twente, Netherlands Guillen et al 10.3389/fnhum.2023.1239105 Frontiers in Human Neuroscience 02 frontiersin.org Ziesel et al, 2023). High-definition (HD) tDCS leverages several small disc electrodes (~6 mm radius) to achieve better focality compared to conventional pad electrodes (Datta et al, 2009).…”
Section: Reviewed Bymentioning
confidence: 99%
“…As an emerging neuromodulation technique, transcranial direct current stimulation (tDCS) has been shown to have therapeutic effects for a wide range of neurological disorders such as major depression ( Bikson et al, 2008 ), epilepsy ( Fregni et al, 2006b ; Auvichayapat et al, 2013 ), Parkinson’s disease ( Fregni et al, 2006a ), chronic pain ( Fregni et al, 2007 ), and stroke ( Meinzer et al, 2016 ). It is shown that tDCS has the potential to promote motor recovery and improve cognitive functions after traumatic brain injury (TBI) ( Kim et al, 2019 ; Schwertfeger et al, 2023 ; Ziesel et al, 2023 ). High-definition (HD) tDCS leverages several small disc electrodes (~6 mm radius) to achieve better focality compared to conventional pad electrodes ( Datta et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation